Model Commercialization of Chips Product at Cluster of Chips at Pojok Cimahi: a Preliminary Study - Crestofel Lantu, Donald; Rosmiati, Mia; Aina, Qorri; Herliana, Sri; Lawiyah, Nur (International Journal of Engineering and Technology, 2018)
Pojok Cimahi is well known as a chips industry in Cimahi City and famous for its various chips products. The cluster that is the main attraction for researchers to further investigate the commercialization model and its business is the chips cluster in Pojok Cimahi. Commercialization is a process that begins with technological insights that end with products that are marketed in a sustainable manner. This study uses qualitative methods and exploration research to SMEs in Pojok Cimahi Clusters, through in-depth interviews of 10 SMEs. The purpose of this research is to know the commercialization model of cluster chips, how the current cluster condition, and what can be recommended for better cluster improvement in the future. Based on the findings, SMEs in the cluster chips in Pojok Cimahi are in the comfort zone. Although in terms of product commercialization through product innovations based on suggestions from customers show a positive and effective in sales, but viewed from the business side there is no further innovative marketing strategy.Â Â